Part of Experimental Researches in Nationally Addressed Lexicography (on the Material of Russian-Mongolian Comparisons) - Alexander S. Mamontov; Enhtuya Tzedendorjiin; Vera V. Boguslavskaya (Polylinguality and Transcultural Practices, 2020)
The purpose of this work is to research significance of experimental procedures usage, in particular so called “psychosemantic” approach in process of nationally addressed educational dictionaries for foreign students, studying language as cross-cultural communication means creation, including a dictionary of values for foreigners. In concrete case we are speaking about the Mongolian students, studying Russian and, accordingly, Russian culture. The investigation is based on principles of comparative Russian-Mongolian cultural values description, received by experimental way. Necessary to underline that in comparative description of the values content it is expediently to proceed from, that content of any linguistic unit is formed by contextual meaning of this unit. Every unit functions in some contexts, therefore in description of any lingual unit usage it is expediently to take into consideration maximum number of context types. In our opinion, it is possible to speak about existence of so-called “Mongolian’s and Russian’s values”. The last plays a considerable role in nationally addressed lexicography (NAL).